Canopy management to improve fruit quality of Coe Red Fuji, Granny Smith and Spartan varieties of apple (Malus domestica) - Mir, Javid Iqbal; Ahmed, Nazeer; Singh, Desh Beer; Sharma, Om Chand; Raja, Waseem Hassan; Shafi, Wajida; Zaffer, Shafia; Jan, Sumaira; Kirmani, S N (The Indian Journal of Agricultural Sciences, 2020)
Light management within apple ( Malus domestica Borkh.) canopies has been an invariable rationale of fruit tree architecture strategy during the development of training systems. This paper attempts to compare fruit quality characteristics of three apple cultivars Coe Red Fuji, Granny Smith and Spartan trained on three canopy architectural engineering (training) system, viz. Espalier, Vertical axis and Cordon were grafted on M 9 rootstock. The maximum fruit weight (210.11g) was observed in Granny Smith and maximum yield per tree (32.11 kg/cm2) and yield efficiency (0.69 kg/cm2) in Coe Red Fuji which may be due to higher crop density. Among training systems, maximum fruit weight (200.12 g), highest yield per tree (36.36 kg) and maximum yield efficiency (0.72 kg/cm2) was observed in espalier training system. The interaction study displayed maximum fruit weight in Granny Smith (210.55g), highest yield per tree in Coe Red Fuji (32.16 kg) and maximum yield efficiency in Spartan on Espalier system. Light interception demonstrated maximum photon flux density (237 µmolm-2 s-1) across the canopy of Spartan with minimum leaf area index (0.30) and among training systems maximum PPFD (221 µmolm-2s-1) was observed in Espalier system with minimum LAI (0.21). Fruit size, TSS and colour parameters of fruits in all varieties were significantly influenced by light intensity. Higher the light intensity, higher was the TSS and colour development in coloured varieties like Spartan and Coe Red Fuji. Therefore, espalier training system was found the best canopy management system allowing maximum PAR penetration and diffusion leading better fruit quality and productivity.